Women who do not speak Spanish: Gender, power and bilingualism in an Andean people - Harvey, Penelope (1991)
The events and practices described in this document took place in Ocongate, a small Andean town in southern Peru. It is a place of great activity, located on the edge of an important road, although not paved, that connects the mountains of southern Peru with the tropical lands of the Amazon. Migrant workers, provisions and raw materials pass daily in the trucks that make the route from Puerto Maldonado to the cities of southern Peru: Cusco, Puno and Arequipa.